Asuhan Keperawatan Keluarga Tn. M dengan Gangguan Sistem Muskuloskeletal : Rheumatoid Arthritis di Desa Kalibuntu RT 02 RW 02 Kecamatan Losari Kabupate Brebes - Nur Huda; Siti Fatimah; Sujono Sujono (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Rheumatoid arthritis is a degenerative disease that attacks the joints, especially in the elderly. The purpose of this paper is to determine and provide nursing care for Mr. M’s family with musculoskeletal system disorders: rheumatoid arthritis in Kalibuntu Village Rt 02 Rw 02 Losari District Brebes Regency according to nursing standards. The method used is a data collection method in the form of interviews, observation, research documentation and physical examination. From the case review, it was found that the client’s main complaint was pain in the nape of the neck and right and left knees especially when waking up, P: pain in the morning when waking up, Q: pain like being cut into pieces, R: nape, right and left knees, S: scale 4, T: intermittent. The nursing problems found were acute pain and knowledge deficit. Interventions were arranged based on the theory in SDKI, SLKI and SIKI as well as on the client’s condition and could be implemented.